Produção científica sobre centro cirúrgico em teses e dissertações: estudo bibliométrico - Alexmália Fiorini da Costa Balonecker; Cintia Silva Fassarella; Priscilla Alfradique de Souza; Ricardo de Oliveira Meneses; Aline Affonso Luna; Mariana Brito de Souza Nunes; Rosilene Alves Ferreira (Revista SOBECC)
Objective: To identify the academic production coming from dissertations and theses about surgical centers by nurses who have completed master’s degrees and doctorates in Brazil. Method: Bibliometric, descriptive and retrospective study, with documentary research in three Brazilian databases, using the publications of 11 higher education institutions, from 2005 to 2016. Results: A total of 40 academic productions were identified. Of these, 13 are theses (32.5%) and 27 are dissertations (67.5%). The years with the most publications (17.5%) were 2009 and 2013. The University of São Paulo and the University of São Paulo — Ribeirão Preto are the institutions with the highest number of studies, with 32.5 and 25.0%, respectively. The methodological approach most adopted by the researchers was the quantitative one (40.0%) and the main theme dealt with perioperative care (60.0%). Conclusion: The scientific production in this area has presented incipient, when compared to the total number of post-graduation publications stricto sensu on nursing in the national scenario. However, what has been published is aimed at hospital care, showing correlation of the studies with the practice of perioperative nursing.